Method for preparing visible-near infrared fluorescent fiber by light induction method and application of visible-near infrared fluorescent fiber

CsPbCl3:Yb3+ perovskite nanomaterials were grown in situ in electrospun fibers by light induction, and the plasma resonance effect of silver nanoparticles was used to solve the problems of perovskite quantum dot stability and preparation complexity, achieving efficient preparation of visible-near-infrared fluorescent fibers, suitable for a variety of photoelectric applications.

CN119710957APending Publication Date: 2025-03-28MINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878520.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The optical performance of perovskite quantum dots has poor stability, complex preparation methods and strict conditions, which limits their practical application.

Method used

CsPbCl3:Yb3+ perovskite nanomaterials were grown in situ in electrospun fibers by light induction, and their luminescent performance was enhanced by the surface plasmon resonance effect of silver nanoparticles.

Benefits of technology

It has achieved significant improvement in the stability and luminous performance of perovskite quantum dots, the preparation process is gentle and simple, suitable for promotion, and is suitable for flexible wearable optoelectronic devices and temperature sensing detection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710957A_ABST
    Figure CN119710957A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a visible-near infrared fluorescent fiber by a photoinduction method and application of the visible-near infrared fluorescent fiber, a perovskite nano material CsPbCl3: Yb3 is grown in a PMMA precursor fiber in situ by an electrostatic spinning method and a photoinduction method, and a CsPbCl3: Yb < 3 + > / AgNCs / PMMA fluorescent fiber is formed. The fluorescent fiber can emit 410 nm blue light and 980 nm near-infrared light under irradiation of 365 nm ultraviolet light, PMMA serving as a protective layer can effectively isolate air and moisture, quenching and oxidation of CsPbCl3: Yb < 3 + > and AgNCs are prevented, and the fluorescent fiber has good stability and flexibility; meanwhile, visible and near-infrared luminescence of CsPbCl3: Yb < 3 + > is remarkably enhanced through the AgNCs surface plasmon resonance effect, and the AgNCs composite material has excellent luminescence performance and can be applied to the fields of temperature sensing detection, near-infrared LED devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of fluorescent fibers, and specifically relates to a method for preparing visible-near infrared fluorescent fibers by light induction and its application. The method uses light induction to in-situ grow CsPbCl3:Yb 3+ Perovskite nanomaterials and using the surface plasmon resonance effect of silver nanoparticles to enhance CsPbCl3:Yb 3+ The obtained fluorescent fiber has good optical properties and stability, and can be used in many fields such as flexible wearable optoelectronic devices, optical temperature sensing, and near-infrared LED devices. Background Art

[0002] All-inorganic perovskite quantum dots have excellent optoelectronic properties, such as high fluorescence quantum yield, narrow half-peak width, tunable emission wavelength, wide spectral range and short radiation lifetime. These advantages make perovskite quantum dots have potential application value in solar cells, X-ray imaging, LED light sources, lasers, photodetectors, backlight displays and other fields. However, the inherent ionization of perovskite quantum dots leads to poor stability of their optical properties; when perovskite quantum dots are converted from solution state to solid devices, the surface ligands are easily lost and defects increase, causing the luminescence efficiency of perovskite quantum dots to decay rapidly; at the same time, perovskite quantum dots are easy to decompose under the influence of the external environment, and are prone to aggregation, fluorescence attenuation or quenching. In addition, traditional perovskite quantum dot preparation methods, including hot injection method, ultrasonic method, solvothermal method and high-temperature solid-phase reaction method, have the disadvantages of complex preparation process, harsh reaction conditions, uncontrollable reaction and long time consumption, which seriously limit the practical application of perovskite quantum dots.

[0003] Based on this, the present invention discloses a method for preparing visible-near infrared fluorescent fiber by light induction method and its application, which uses polymethyl methacrylate (PMMA), carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and silver nanocubic particles (AgNCs) as raw materials, and prepares PMMA precursor fiber containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs by electrospinning method. On this basis, the perovskite nanomaterial CsPbCl3:Yb is in situ grown in the PMMA precursor fiber by light induction method. 3+ , forming CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fiber. The fluorescent fiber can emit 410nm blue light and 980nm near-infrared light under 365nm ultraviolet light. PMMA as a protective layer can effectively isolate air and moisture to prevent CsPbCl3:Yb 3+and AgNCs quenching and oxidation, and has good stability and flexibility; at the same time, the surface plasmon resonance effect of AgNCs significantly enhances the 3+ It emits visible and near-infrared light and has excellent luminescence properties, and can be used in temperature sensing, near-infrared LED devices and other fields. Summary of the invention

[0004] In order to overcome the inherent light sensitivity of perovskite quantum dots to the environment, poor stability, complex preparation process, harsh reaction conditions, uncontrollable reactions and other problems, the purpose of the present invention is to propose a method for preparing visible-near-infrared fluorescent fibers by light-induced method and its application, so as to overcome the shortcomings of the prior art.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing visible-near infrared fluorescent fiber by light induction method comprises the following steps: PMMA precursor fibers containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate, and silver nanocubic particles (AgNCs) were prepared by electrospinning with polymethyl methacrylate (PMMA), carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate, and AgNCs as raw materials. On this basis, the perovskite nanomaterial CsPbCl3:Yb was in situ grown in the PMMA precursor fibers by the photoinduced method. 3+ , forming CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fiber, which can emit 410 nm blue light and 980 nm near-infrared light under 365 nm ultraviolet light. PMMA as a protective layer can effectively isolate air and moisture to prevent CsPbCl3:Yb 3+ and AgNCs quenching and oxidation, and has good stability and flexibility; at the same time, the surface plasmon resonance effect of AgNCs significantly enhances the 3+ It has excellent visible and near-infrared luminescence properties.

[0006] Furthermore, the method for preparing visible-near infrared fluorescent fiber by light induction method comprises the following steps: (1) Take 1.5-2.0 g of PMMA and add it to 3-4 mL of N,N-dimethylformamide solvent. Heat it to 40-60 °C and stir it at 500-600 rpm for 10-12 h to completely dissolve the PMMA to obtain a PMMA spinning solution.

[0007] (2) Mix 10-20 μL of cesium oleate solution, 10-20 μL of lead oleate solution, 10-20 μL of ytterbium oleate solution, and 2-4 mL of carbon tetrachloride. Add 500-1000 μL of the mixed solution and 50-100 μL of 0.15-0.20 mmol / mL AgNCs ethanol solution to the PMMA spinning solution prepared in step (1). Stir at 900-1000 rpm for 10-15 min to obtain a PMMA spinning solution containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs.

[0008] (3) The PMMA spinning solution prepared in step (2) is used to prepare PMMA fibers by an electrospinning method. The electrospinning conditions are as follows: spinning voltage is 16-18 kV, feed rate is 250-300 μL / h, receiving distance is 4-6 cm, spinning time is 15-30 min, and PMMA precursor fibers containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs are obtained.

[0009] (4) The PMMA precursor fiber prepared in step (3) was irradiated under a 365 nm ultraviolet lamp with a power of 5 W for 30 to 45 min, and CCl4 was decomposed under 365 nm ultraviolet light and provided Cl‾ ions to react with Pb 2+ Ion, Cs + Ion and Yb 3+ Ions combine to form perovskite quantum dots CsPbCl3:Yb 3+ , thus obtaining CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fibers.

[0010] Furthermore, the silver nanocubic particles are prepared by using glycerol as a reducing agent, sodium chloride as a controlling agent, polyvinyl pyrrolidone as a surfactant, and silver nitrate as a silver source to rapidly synthesize the silver nanocubic particles by a solvothermal method. The specific preparation method is as follows: (1) Prepare 0.15-0.20 g / mL polyvinyl pyrrolidone solution, 0.10-0.12 g / mL silver nitrate solution, and 0.02-0.03 g / mL sodium chloride solution; (2) Take 2-3 mL of polyvinyl pyrrolidone solution, 0.5-1 mL of sodium chloride solution, 2-3 mL of silver nitrate solution and 2-3 mL of glycerol, mix them evenly, react at 160-165 °C for at least 2 h, and after cooling, obtain a silver nanocubic particle solution; (3) The silver nanocubic particle solution prepared in step (2) is centrifuged at 7500-8000 rpm for 8-10 min, washed with anhydrous ethanol 2-3 times, and dispersed in 3-5 mL of anhydrous ethanol to obtain an ethanol solution of silver nanocubic particles.

[0011] Furthermore, the preparation of the cesium oleate solution, the lead oleate solution, and the ytterbium oleate solution is carried out using oleylamine, oleic acid, 1-octadecene, cesium carbonate, lead acetate, and ytterbium acetate as raw materials in a vacuum atmosphere to prepare the cesium oleate solution, the lead oleate solution, and the ytterbium oleate solution. The specific preparation method is as follows: (1) Weigh 0.642-0.662 g of cesium carbonate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene in a three-necked round-bottom flask, evacuate the flask, and heat to 120-125 °C for at least 30 min, then heat to 145-150 °C for at least 20 min, and cool to room temperature to obtain a cesium oleate solution.

[0012] (2) Weigh 1.410-1.612 g of lead acetate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene in a three-necked round-bottom flask, evacuate the flask, and heat to 120-125 °C for at least 30 min, then heat to 145-150 °C for at least 20 min, and cool to room temperature to obtain a lead oleate solution.

[0013] (3) Weigh 1.589-1.789 g of ytterbium acetate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene into a three-necked round-bottom flask, evacuate the flask, and heat to 120-125 °C for at least 30 min. Heat to 145-150 °C for at least 20 min, and cool to room temperature to obtain an ytterbium oleate solution.

[0014] Furthermore, applications: Visible-near infrared fluorescent fibers can be used in temperature sensing and near infrared LED devices.

[0015] In the present invention, perovskite quantum dots are coated in polymer fibers to improve the stability of perovskite quantum dots, which can inhibit the fluorescence quenching caused by the aggregation of perovskite quantum dots, and can control the size of perovskite quantum dots in polymer fibers to improve their optical properties. At the same time, polymer fibers can isolate air, water, etc., making them have excellent flexibility and convenient processability. The photoinduced method for preparing perovskite quantum dots uses halogenated alkanes as inactive halogen sources. Under ultraviolet light (365 nm), the covalent carbon-halogen (CX) bonds of halogenated alkanes gradually break and provide halogen ions, which can react with Pb in the reaction solution. 2+ Ion, Cs + Ion and Yb3+ The combination of ions forms perovskite quantum dots. Compared with the traditional perovskite quantum dot synthesis method, the light-induced method has the advantages of mild and simple preparation conditions, green and environmental protection, slow reaction rate, and easy regulation of perovskite size.

[0016] On the other hand, the surface plasmon resonance effect of AgNCs can enhance the luminescence performance of perovskite quantum dots. The local field enhancement effect of the localized surface plasmon of AgNCs materials can confine the energy of incident light to a deep subwavelength or even nanoscale spatial range, thereby greatly enhancing the energy density of light and the local electric field intensity, forming the so-called "hot spot". When the resonant wavelength of the surface plasmon is close to the excitation wavelength of the perovskite quantum dots, the excitation efficiency can be improved; when it is close to the emission wavelength of the perovskite quantum dots, the emission efficiency can be improved. This enhancement of the local electric field can significantly improve the excitation efficiency or emission efficiency of the perovskite quantum dots, thereby enhancing the luminescence performance of the perovskite quantum dots.

[0017] Compared with the prior art, the present invention has the following advantages and effects: (1) The present invention uses PMMA fiber as a substrate and in-situ grows perovskite quantum dots in the PMMA fiber to prevent the perovskite quantum dots from aggregating and causing fluorescence quenching. At the same time, the PMMA fiber provides a good protective layer to isolate the external environment and improve the luminescence stability of the perovskite quantum dots.

[0018] (2) The present invention utilizes the sharp edges of silver nanocubic particles to generate a significantly enhanced local field. The local field enhancement effect can significantly improve the excitation efficiency or emission efficiency of perovskite quantum dots and improve the luminescence performance of perovskite quantum dots.

[0019] (3) The present invention has the advantages of mild and simple preparation conditions, green and environmental protection, easy operation, low cost, slow reaction rate, and easy regulation of the size of perovskite quantum dots, and is suitable for promotion.

[0020] (4) CsPbCl3:Yb prepared by the present invention 3+ / AgNCs / PMMA fluorescent fibers have good flexibility and have broad application prospects in flexible wearable optoelectronic devices, optical temperature sensors, LED devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the process of preparing visible-near infrared fluorescent fibers by the light-induced method of the present invention; Figure 2 This is a SEM image of the silver nanocubic particles prepared in the present invention; Figure 3The electronic photographs of the visible-near infrared fluorescent fiber prepared by the present invention under (a) natural light and (b) 365nm ultraviolet light, wherein (b) is the luminescence of the fluorescent fiber at different bending angles; Figure 4 This is a SEM image of the visible-near infrared fluorescent fiber prepared by the present invention; Figure 5 The luminescence spectrum of the visible-near infrared fluorescent fiber prepared by the present invention; Figure 6 The luminescence spectra of the visible-near infrared fluorescent fiber prepared by the present invention at different storage times; Figure 7 Application of the visible-near infrared fluorescent fiber prepared by the present invention in temperature sensing: (a) luminescence spectra at different temperatures; (b) relationship between fluorescence intensity ratio FIR and temperature; (c) absolute sensitivity S a and relative sensitivity S r Plotted against temperature; Figure 8 Application of the visible-near-infrared fluorescent fiber prepared by the present invention in near-infrared LED devices: electronic photos of (a) the toy and (b) the reagent bottle taken with a common camera and a near-infrared camera under natural light and near-infrared LED, respectively; the illustration of (a) is a photo of the luminescence of the prepared near-infrared LED device taken with a near-infrared camera. DETAILED DESCRIPTION

[0022] In order to further disclose but not limit the present invention, the present invention is further described in detail below in conjunction with embodiments.

[0023] Example 1 The process of preparing visible-near infrared fluorescent fibers by light induction method is as follows: Figure 1 As shown, the following steps are included: (1) Prepare 2 mol / L polyvinyl pyrrolidone solution, 0.67 mol / L silver nitrate solution, and 0.17 mol / L sodium chloride solution; take 3 mL of polyvinyl pyrrolidone solution, 3 mL of silver nitrate solution, 1 mL of sodium chloride solution, and 2 mL of glycerol, mix them thoroughly, react at 160 °C for 2 h, and cool to obtain a silver nanocubic particle solution. Centrifuge the obtained solution at 7000 rpm for 8 min, wash with anhydrous ethanol, repeat 3 times, and then disperse in anhydrous ethanol to obtain an ethanol solution of silver nanocubic particles.

[0024] (2) Add 0.662 g of cesium carbonate, 4 mL of oleic acid, 4 mL of oleylamine and 12 mL of 1-octadecene into a 100 mL three-necked round-bottom flask. Heat to 120 °C under stirring and vacuum conditions for 30 min, then heat to 150 °C and hold for 20 min to obtain a cesium oleate solution.

[0025] (3) Add 1.612 g of lead acetate, 4 mL of oleic acid, 4 mL of oleylamine and 12 mL of 1-octadecene into a 100 mL three-necked round-bottom flask. Heat to 120 °C under stirring and vacuum conditions for 30 min, then heat to 150 °C and hold for 20 min to obtain a lead oleate solution.

[0026] (4) Add 1.789 g of ytterbium acetate, 4 mL of oleic acid, 4 mL of oleylamine and 12 mL of 1-octadecene into a 100-mL three-necked round-bottom flask and heat to 120 °C under stirring and vacuum conditions for 30 min. Then, heat to 150 °C and hold for 20 min to obtain an ytterbium oleate solution.

[0027] (5) Take 1.5 g of PMMA and add it into 3 mL of N,N-dimethylformamide solvent. Stir at 600 rpm at 60 °C for 10 h to completely dissolve the PMMA to obtain a PMMA spinning solution.

[0028] (6) Take 20 μL of cesium oleate solution, 20 μL of lead oleate solution, 20 μL of ytterbium oleate solution, and 2 mL of carbon tetrachloride into a beaker and mix well. Take 1 mL of the mixed solution and 100 μL of 0.15 mmol / mL AgNCs ethanol solution and add them to the PMMA spinning solution. Stir at 1000 rpm for 15 min to obtain a PMMA spinning solution containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs.

[0029] (7) The prepared PMMA spinning solution was used to prepare PMMA fibers by an electrospinning method. The electrospinning conditions were as follows: spinning voltage of 16 kV, feed rate of 250 μL / h, receiving distance of 6 cm, and spinning time of 20 min. PMMA precursor fibers containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs were obtained.

[0030] (8) The prepared PMMA precursor fiber was irradiated under a 365 nm ultraviolet lamp with a power of 5 W for 40 min. CCl4 was decomposed under 365 nm ultraviolet light and provided Cl‾ ions to react with Pb 2+ Ion, Cs + Ion and Yb 3+The ions combine to form CsPbCl3:Yb 3+ , thus obtaining CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fibers.

[0031] Figure 2 This is the SEM image of the prepared silver nanocubic particles. It can be seen from the figure that the prepared silver nanocubic particles are uniform in size, regular in morphology, good in dispersion, without obvious agglomeration, and the side length is about 90 nm.

[0032] Figure 3 This is an electronic photograph of the visible-near infrared fluorescent fiber prepared by the present invention. Figure 3 From a, we can see that under natural light, the surface of the prepared fluorescent fiber film is smooth; Figure 3 It can be seen that under the irradiation of 365 nm ultraviolet light, blue light visible to the naked eye is emitted. At the same time, obvious blue light emission can be observed under different degrees of bending, indicating that the prepared fluorescent fiber has good flexibility.

[0033] Figure 4 The SEM image of the prepared visible-near infrared fluorescent fiber is Figure 4 As shown in a, the prepared fluorescent fiber is composed of many randomly arranged nanowires, each of which has uniform thickness and an average diameter of about 500nm. Figure 4 As can be seen in b, silver nanocubic particles and CsPbCl3:Yb 3+ Perovskite nanoparticles are evenly distributed in PMMA fibers, demonstrating the successful in situ growth of CsPbCl3:Yb in PMMA fibers using the photoinduced method. 3+ Nanoparticles.

[0034] Figure 5 The luminescence spectrum of the prepared visible-near infrared fluorescent fiber under 365 nm ultraviolet light excitation shows that there are two obvious emission characteristic peaks, located at 410 nm and 980 nm, corresponding to CsPbCl3:Yb 3+ The exciton emission of the samples is related to the Yb 3+ Ionic 2 F 5 / 2 → 2 F 7 / 2 When 100 μL of silver nanocubic particles were added, the luminescence intensity of the fluorescent fiber was significantly enhanced by 7.8 times. This is because the local field enhancement effect of silver nanocubic particles can significantly increase the energy level of CsPbCl3:Yb 3+ The excitation efficiency and emission efficiency of the excitons are 3+ ions, thereby enhancing the CsPbCl3:Yb 3+Visible and near-infrared luminescence properties.

[0035] Figure 6 The luminescence spectra of the prepared visible-near-infrared fluorescent fiber at different storage times are shown in the figure. As can be seen from the figure, after the fluorescent fiber is stored in the air for 10 days, the luminescence intensity remains basically unchanged, indicating that the PMMA fiber is CsPbCl3:Yb 3+ It provides a good protective layer, which can isolate air, water, etc. and reduce CsPbCl3:Yb 3+ The surface defects of nanoparticles ensure that CsPbCl3:Yb 3+ Luminescence stability.

[0036] Figure 7 The application of the prepared visible-near infrared fluorescent fiber in temperature sensing is demonstrated by Figure 7 As shown in Figure a, as the temperature rises from 297 K to 337 K, the Yb 3+ The luminescence intensity of Yb ions (980 nm) decreased significantly, while that of CsPbCl3 excitons (410 nm) did not decrease significantly, which proved that 3+ ions and CsPbCl3 excitons have temperature sensing properties. 3+ The ratio of the luminescence intensity to the exciton luminescence intensity is defined as the fluorescence intensity ratio (FIR). The relationship between FIR and temperature (T) can be expressed as (1) Where A and C are constants. B = ΔE / k B , where ΔE is the energy difference between the thermal coupling energy levels, k B and T are the Boltzmann constant and absolute temperature, respectively. The absolute sensitivity (S) of FIR-based temperature sensing a ) and relative sensitivity (S r )for (2) (3) Depend on Figure 7 As can be seen in Figure b, in the temperature range of 297 K to 337 K, the FIR value of the prepared fluorescent fiber continues to increase with the increase of temperature, and the fitting coefficient is R 2 =0.993. Figure 7 The c in the figure is the temperature sensing Sa and Sr. The maximum Sr is 2.1% K at 297 K. -1 , the maximum Sa is 0.28 K at 337 K -1 .

[0037] Figure 8The application of the prepared fluorescent fiber in near-infrared LED devices. The fluorescent fiber is combined with a commercial ultraviolet InGaN chip to make a near-infrared LED device, such as Figure 8 As shown in the illustration in middle a, during the operation of the near-infrared LED device, the ultraviolet light emitted by the commercial InGaN chip can effectively excite the fluorescent fiber and produce bright near-infrared light. Figure 8 Figures a and b are electronic photos of the toy and reagent bottle taken by an ordinary camera and a near-infrared camera under natural light and near-infrared LED illumination, respectively. As can be seen from the figure, once the near-infrared LED device is lit, it is easy to capture black and white images of the toy and reagent bottle through the near-infrared camera, which is consistent with the color image captured by the ordinary camera, proving that the application of the prepared fluorescent fiber in the near-infrared LED device is feasible.

[0038] In summary, the present invention combines PMMA fiber with CsPbCl3:Yb 3+ The combination of nanomaterials and silver nanoparticles prevents the quenching caused by the aggregation of perovskites in PMMA fibers, and controls the size of perovskites to improve their optical properties. Electrospinning can fix silver nanocubic particles and perovskite luminescent materials in the fibers, which can not only isolate air and water to improve the luminescent properties of perovskites, but also be flexible and cuttable. The local field enhancement properties of the local surface plasma of silver nanocubic particles are used to achieve the CsPbCl3:Yb 3+ The fluorescence enhancement can be applied to temperature sensing and near-infrared LED devices.

[0039] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing visible-near infrared fluorescent fibers by light induction, characterized in that: PMMA precursor fibers containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate, and silver nanocubic particles AgNCs were prepared by electrospinning. On this basis, the perovskite nanomaterial CsPbCl3:Yb was in situ grown in the PMMA precursor fibers by photoinduced method. 3+ , forming CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fiber, which can emit 410 nm blue light and 980 nm near-infrared light under 365 nm ultraviolet light. PMMA as a protective layer can effectively isolate air and moisture to prevent CsPbCl3:Yb 3+ and AgNCs quenching and oxidation; the surface plasmon resonance effect of AgNCs significantly enhances the 3+ Visible and near-infrared luminescence.

2. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 1, characterized in that: The following steps are involved: (1) Take 1.5-2.0 g of PMMA and add it to 3-4 mL of N,N-dimethylformamide solvent, heat it to 40-60 °C, and stir it at 500-600 rpm for 10-12 h to completely dissolve the PMMA to obtain a PMMA spinning solution; (2) Mix 10-20 μL of cesium oleate solution, 10-20 μL of lead oleate solution, 10-20 μL of ytterbium oleate solution and 2-4 mL of carbon tetrachloride, take 500-1000 μL of the mixed solution and 50-100 μL of 0.15-0.20 mM AgNCs solution and add them to the PMMA spinning solution prepared in step (1), stir at 900-1000 rpm for 10-15 min, and obtain a PMMA spinning solution containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs; (3) preparing PMMA fibers by an electrospinning method using the PMMA spinning solution prepared in step (2), wherein the electrospinning conditions are as follows: spinning voltage of 16-18 kV, feed rate of 250-300 μL / h, receiving distance of 4-6 cm, spinning time of 15-30 min, and obtaining PMMA precursor fibers containing carbon tetrachloride, cesium oleate, lead oleate, ytterbium oleate and AgNCs; (4) The PMMA precursor fiber prepared in step (3) was irradiated under a 365 nm ultraviolet lamp with a power of 5 W for 30 to 45 min, and carbon tetrachloride was decomposed under the 365 nm ultraviolet light to provide Cl‾ ions, which reacted with Pb 2+ Ion, Cs + Ion and Yb 3+ Ions combine to form perovskite quantum dots CsPbCl3:Yb 3+ , thus obtaining CsPbCl3:Yb 3+ / AgNCs / PMMA fluorescent fibers.

3. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 2, characterized in that: Silver nanocubic particles AgNCs were prepared by a solvothermal method using glycerol as a reducing agent, sodium chloride as a controlling agent, polyvinyl pyrrolidone as a surfactant, and silver nitrate as a silver source to rapidly synthesize silver nanocubic particles.

4. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 3, characterized in that: The preparation method of silver nanocubic particles AgNCs comprises the following steps: (1) Prepare 0.15-0.20 g / mL polyvinyl pyrrolidone solution, 0.10-0.12 g / mL silver nitrate solution, and 0.02-0.03 g / mL sodium chloride solution; (2) Take 2-3 mL of polyvinyl pyrrolidone solution, 0.5-1 mL of sodium chloride solution, 2-3 mL of silver nitrate solution and 2-3 mL of glycerol, mix them evenly, react at 160-165 °C for at least 2 h, and after cooling, obtain a silver nanocubic particle solution; (3) The prepared silver nanocubic particle solution was centrifuged at 7500-8000 rpm for 8-10 min, and washed with anhydrous ethanol 2-3 times to obtain silver nanocubic particles.

5. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 2, characterized in that: The preparation of cesium oleate solution, lead oleate solution and ytterbium oleate solution is carried out by taking oleylamine, oleic acid, 1-octadecene and cesium carbonate or lead acetate or ytterbium acetate as raw materials respectively under vacuum atmosphere to prepare cesium oleate solution, lead oleate solution and ytterbium oleate solution.

6. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 5, characterized in that: The specific preparation method of the cesium oleate solution includes: weighing 0.642-0.662 g of cesium carbonate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene, mixing, evacuating and heating to 120-125° C., maintaining for at least 30 min, heating to 145-150° C., maintaining for at least 20 min, and naturally cooling to room temperature to obtain a cesium oleate solution.

7. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 5, characterized in that: The specific preparation method of the lead oleate solution comprises: weighing 1.410-1.612 g of lead acetate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene, mixing, evacuating and heating to 120-125° C., maintaining for at least 30 min, heating to 145-150° C., maintaining for at least 20 min, and naturally cooling to room temperature to obtain the lead oleate solution.

8. The method for preparing visible-near infrared fluorescent fiber by light induction method according to claim 5, characterized in that: The specific preparation method of the ytterbium oleate solution comprises: weighing 1.589-1.789 g of ytterbium acetate, 4-6 mL of oleic acid, 4-6 mL of oleylamine, and 10-12 mL of 1-octadecene, mixing, evacuating and heating to 120-125° C., maintaining for at least 30 min, heating to 145-150° C., maintaining for at least 20 min, and naturally cooling to room temperature; obtaining the ytterbium oleate solution.

9. Visible-near infrared fluorescent fiber obtained according to the preparation method according to any one of claims 1 to 8.

10. An application of the visible-near infrared fluorescent fiber as claimed in claim 9, characterized in that: Visible-near infrared fluorescent fibers are used in the fields of temperature sensing and near infrared LED devices.